Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(2x + 5)(2x - 7) - (2x - 3)2 = 36
4x2 - 14x + 10x - 35 - 4x2 + 12x - 9 = 36
8x - 44 = 36
8x = 36 + 44
8x = 80
x = 10
a) 1212-212=(121-21)(121+21)=100.142=14200
b) 20102-10102=(2010-1010)(2010+1010)=1000.3030=3030000
Hết
a) 2x3-5x2+8x-3
=2x3-x2-4x2+2x+6x-3
=x2(2x-1)-2x(2x-1)+3(2x-1)
=(2x-1)(x2-2x+3)
a,2x3-5x2+8x-3
=2x3-x2-4x2+2x+6x-3
=x2(2x-1)-2x(2x-1)+3(2x-1)
=(2x-1)(x2-2x+3)
\(50^2-49^2+48^2-47^2+........+2^2-1^2.\)
\(=\left(50+49\right)\left(50-49\right)+\left(48+47\right)\left(48-47\right)+........+\left(2+1\right)\left(2-1\right)\)
\(=49+50+48+47+.....+2+1\)
\(=49\div2\times50=1225\)
\(-6x^3+x^2-5x-2=-6x^3-2x^2+3x^2+x-6x-2\)
\(=-2x^2\left(3x+1\right)+x\left(3x+1\right)-2\left(3x+1\right)=\left(3x+1\right)\left(-2x^2+x-2\right)\)
\(50^2-49^2+48^2-47^2+46^2-45^2+...+2^2-1^2\)
\(=\left(50+49\right)\left(50-49\right)+\left(48+47\right)\left(48-47\right)+...+\left(2+1\right)\left(2-1\right)\)
\(=49+50+48+47+...+2+1\)
\(=49\div2\times50\)
\(=1225\)
= 9,7(10,3-0,3)+10,3(10,3-0,3)
=9,7x10+10,3x10
=97+103
=200
10,3 . 9,7 - 9,7 . 0,3 + 10,32 - 10,3 . 0,3
= 10,3 . (9,7 + 10,3) - 0,3 . (9,7 + 10,3)
= 10,3 . 20 - 0,3 . 20
= 20 . (10,3 - 0,3)
= 20 . 10
= 200
Dễ mà :3
Chúc bạn học tốt!